Cytokine expression during pig pregnancy (Veterinary Science, 2022)
Pig production in Argentina is constantly growing. Reproductive management is essential to achieve optimal birth rates that translate into greater profitability and investment efficiency. Prenatal losses limit pig production. Alterations in the migration of the embryos, elongation, immunological recognition of pregnancy by the mother and embryonic competition for the implantation site can arise in this process. In a successful pregnancy, the dialogue established between the conceptus and the endometrium involves, among others, the immune system and its main molecules called cytokines. Cytokines are a group of low molecular weight proteins that mediate complex interactions between different cell types. Numerous studies describe the role of various cytokines that are involved in the regulation of the inflammatory process characteristic of the fetus/maternal interface throughout the normal pig pregnancy. This review describes the main cytokines that act during pig pregnancy, both in the early gestation period and in the late pregnancy period.
Keywords: Pigs; Gestation; Cytokines; mmunology; Immunology; Reproduction